BERBAGAI JENIS NEAR-RING DAN KETERKAITANNYA - Pranadita Sitaresmi (Jurnal Matematika, 2016)
Let be a non empty set with two binary operations, those are additive and multiplicative. Triple  is near-ring if is a group structure toward additive operation, semigroup structure toward multiplicative operation and statisfied right distributive law toward that both binary operation.  is said to be regular if for every  there exists  such that . If  is a group  is called a near field. Near ring  is said to be  near ring if for every  there exists  such that  and said to be  near ring if for every  there exists  such that . Futhermore, disscussed the relation between  near ring and  near ring with regular near ring and near field. Every near field are ,  near ring. Every regular near ring  is an  near ring and if  is weak commutative then  is an  near ring.